Impact of patient cost sharing on medication adherence among asthmatic patients on dual‐controller therapy. Issue 4 (3rd October 2013) - Vaidya, Varun; Tak, Sunghee; Hong, Song Hee
Abstract: Introduction: Asthmatic patients are at risk for poor medication adherence when cost sharing keeps patients from accessing required controller medications. The risk for poor medication adherence would be even higher when asthmatic patients are in need of multiple controller drugs. This study aimed to quantify the effect of cost‐sharing levels on medication adherence among asthmatic patients in the USA who were initiated on dual‐controller therapies. Methods: This study was a retrospective cohort study. Using a large administrative commercial claims and encounters dataset (MarketScan), patients who were initiated on dual‐controller therapy (inhaled corticosteroids and long‐acting beta‐2‐agonist or inhaled corticosteroids and leukotriene receptor antagonist) during 1 July 2000 and 30 June 2001 were identified from pharmacy claims. For asthmatic patients aged 6–65 years, medication adherence (i.e., medication possession ratio) was measured in a 1‐year follow‐up period. Patients' average out‐of‐pocket expenses were determined for a month's supply and then stratified into the following four categories: US$0–15, US$16–30, US$31–45 and >US$45. Logistic regression analysis was used to estimate odds ratio (OR) for medication adherence. Results: Altogether, 1447 patients met the study criteria. Of these patients, 898 (62.1%) were initiated on inhaled corticosteroids and long‐acting beta‐2‐agonist, and 549 (37.9%) were initiated on inhaled corticosteroids and leukotriene receptor antagonist. The study showed significant association of cost‐sharing levels and poor medication adherence. Compared with patients on US$0–15 cost‐sharing level, patients on US$16–30 (OR = 0.449, 95% confidence interval (CI) = 0.312–0.616), US$31–45 (OR = 0.246, 95% CI = 0.168–0.358) and US$46 or higher (OR = 0.131, 95% CI = 0.084–0.206) levels all had lower odds of acceptable medication adherence. Conclusions: Cost sharing was associated with poor medication adherence among asthmatic patients who needed dual controllers. Healthcare providers and payers should take caution when asthmatic patients face increased levels of cost sharing to fill prescription for dual controllers.